Perception, Trust, and Motivation in Consumer Behavior for Organic Food Acquisition: An Exploratory Study - Elena Moroșan; Violeta Popovici; Ioana Andreea Popescu; Adriana Daraban; Oana Karampelas; Liviu Marian Matac; Monica Licu; Andreea Rusu; Larisa-Marina-Elisabeth Chirigiu; Sinziana Opriţescu; Elena Iuliana Ionita; Alina Saulean; et al. (Foods)
(1) Background: A sustainable healthy diet assures human well-being in all life stages, protects environmental resources, and preserves biodiversity. This work investigates the sociodemographic factors, knowledge, trust, and motivations involved in organic food acquisition behavior. (2) Methods: An online survey via Google Forms platform, with 316 respondents, was conducted from 1 March to 31 May 2024. (3) Results: Our findings show that suitably informed people with high educational levels (academic and post-college) report significant satisfaction with organic food consumption (p < 0.05). There is also a considerable correlation between ages 25–65, moderate to high satisfaction, and “yes” for eco-food recommendations (p < 0.05). The same satisfaction levels are associated with medium confidence in eco-food labels and a moderate to high monthly income (p < 0.05). Our results show that monthly income and residence are not essential factors in higher price perception. Insignificant price variation perception correlated with high confidence and weekly acquisition (p < 0.05). Similar price perception correlates with the highest confidence level and daily acquisition (p < 0.05). Obese respondents exhibited minimal satisfaction and opted for “abstention” from eco-food recommendations (p < 0.05). (4) Conclusions: The present study extensively analyzed Romanian people’s knowledge, perception, and trust regarding organic foods. It demonstrates that sociodemographic factors differentiate consumers and influence attitudes and motivation for organic food acquisition.